The N250 Brain Potential to Personally Familiar and Newly Learned Faces and Objects - Pierce, Lara J.; Scott, Lisa; Boddington, Sophie; Droucker, Danielle; Curran, Tim; Tanaka, Jim (Frontiers in Human Neuroscience, 2011)
Studies employing event-related potentials (ERPs) have shown that when participants are monitoring for a novel target face, the presentation of their own face elicits an enhanced negative brain potential in posterior channels approximately 250 ms after stimulus onset. Here, we investigate whether the own-face N250 effect generalizes to other highly familiar objects, specifically, images of the participant’s own dog and own car. In our experiments, participants were asked to monitor for a pre-experimentally unfamiliar target face (Joe), a target dog (Experiment 1: Joe’s Dog) or a target car (Experiment 2: Joe’s Car). The target face and object stimuli were presented with non-target foils that included novel face and object stimuli, the participant’s own face, their own dog (Experiment 1) and their own car (Experiment 2). The consistent findings across the two experiments were the following: 1) the N250 potential differentiated the target faces and objects from the non-target face and object foils and 2) despite being non-targets, the own face and own objects produced an N250 response that was equal in magnitude to the target faces and objects by the end of the experiment. Thus, as indicated by its response to personally familiar and recently familiarized faces and objects, the N250 component is a sensitive index of individuated representations in visual memory.